Development of Ebook Teaching Materials Based on the PBL Model Assisted by the Kvisoft Flibbook Maker Application in Class IV Elementary Schools - Putri, Aprien Rahma; Desyandri; Ahmad, Syafri; J, Fetri Yeni; AD, Riduan; Ernawati (Postgraduate, University of Mataram, 2024)
This research was conducted because of several findings in the field in the form of technological devices, facilities and infrastructure that are still not being utilized optimally by teachers in the learning process to support interesting and enjoyable learning. E-book teaching material based on the PBL model assisted by the kvisoft flipbook maker application in class IV elementary school which is valid, practical and effective as a solution to overcome the problems found in initial observations. This research activity uses a type of Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model. At the analysis stage, observations and interviews were carried out with teachers and students at three schools, namely SDS IT Dar El Iman, SDIT Sabihisma 1, and SDIT Sabihisma 2, Padang city. At the design stage, a teaching material was designed based on the facts obtained. At the development stage, the teaching material that had been designed was validated to find out whether the product was valid for implementation expert validators (material, language and media) as well as one expert from the FGD teacher so that an overall average validation result of 89.33% was obtained with a very valid category. The results obtained after evaluating the practicality test of the teacher response questionnaire with an average score of 93.30% were in the very practical category and the student response questionnaire obtained an average score of 88.59% which was in the very practical category. In the effectiveness test, the learning outcomes obtained an average score of 91.16 with an N-Gain Score of 67.15%, including the quite effective category.